2015
DOI: 10.1038/bmt.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Second allo-SCT in patients with lymphoma relapse after a first allogeneic transplantation. A retrospective study of the EBMT Lymphoma Working Party

Abstract: The aim of this registry-based retrospective study was to analyze the outcome of second allogeneic hematopoietic SCT (alloHSCT_2) performed in patients with lymphoma who had relapsed after a first allogeneic transplant (alloHSCT_1). Patients ⩾ 18 years who had received an alloHSCT_2 for lymphoma relapse between 2000 and 2011 were eligible. One hundred and forty patients were identified. The diagnosis was Hodgkin lymphoma (HL) in 31%, diffuse large B-cell lymphoma in 14%, T-cell lymphoma in 12%, indolent lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This has been particularly relevant with PTCy, given the significant rate of disease relapse observed. Although in our study overall efficacy is difficult to assess given the small [60][61][62][63] . Indeed, in our cohort 42% of patients receiving haploidentical HSCT2 for leukemia relapse after allogeneic transplantation could be rescued, with low rates of NRM.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…This has been particularly relevant with PTCy, given the significant rate of disease relapse observed. Although in our study overall efficacy is difficult to assess given the small [60][61][62][63] . Indeed, in our cohort 42% of patients receiving haploidentical HSCT2 for leukemia relapse after allogeneic transplantation could be rescued, with low rates of NRM.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…reported that 17 patients with T-cell lymphoma underwent the second allo-HSCT and 5-year cumulative PFS after second allo-HSCT was 27%. [ 35 ] Chemosensitivity at the second allo-HSCT and interval between the two allo-HSCT (longer than 12 months or not) are significant risk factors for OS and PFS. This study provides first document for T-cell lymphoma that a second allo-HSCT can achieve long-term survival in a substantial fraction of patients with relapsed disease after first allo-HSCT.…”
Section: T Reatment P Rinciple For mentioning
confidence: 99%
“…Recently, the LWP of the EBMT has reported [ 41 ] the results on the outcome of the second allo-SCT (allo-SCT-2) performed in one hundred and forty patients with lymphoma, of which 31% were affected by HL. Three-year PFS, OS, relapse incidence, and NRM were 19%, 29%, 58%, and 23%, respectively.…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 99%